Modelo de cuidado para el desarrollo sostenible en comunidades rurales del Perú - Rodríguez Quezada, María Del Pilar (2015)
Objective of this thesis was to systematize a model of care for the sustainable development of the rural communities of the Peru. The research is qualitative cutting critico-historico dialectic, with exploratory and multicentre approach allowing to compare the model of development of the rural communities in the regions coast, mountains and jungle of the Peru through the approaches of knowledge of sociocultural determinations associated with development, which were collected during the year 2013 of the families through the questionnaire and of the stakeholders through the interview with depth and thus decrypt aspects that the appearance failed to disclose and that later served for the construction of the Rainbow Model of the Care for Rural Community Development, which is based on the approaches of capacities, sustainable human development, gender, human rights and multiculturalism and is structured in 4 cross-cutting themes: identity capacity, social responsibility capacity, participation and citizenship capacity and research capacity, Whereas, as public policy, intersectoral coordination with the community and the government.